2022
DOI: 10.3390/insects13040328
|View full text |Cite
|
Sign up to set email alerts
|

Field Suppression of Spotted Wing Drosophila (SWD) (Drosophila suzukii Matsumura) Using the Sterile Insect Technique (SIT)

Abstract: Drosophila suzukii (spotted wing drosophila—SWD) is an economically important pest of soft and stone fruit worldwide. Control relies on broad-spectrum insecticides, which are neither fully effective nor environmentally sustainable. The sterile insect technique (SIT) is a proven, effective and environmentally friendly pest-management tool. Here, we investigated, for the first time, the potential of using SIT to control D. suzukii in field conditions without physical barriers that limit insect invasion. A propri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Consistent releases of sterile males could outcompete fertile males with the aim of reducing populations of D. suzukii in the crop. This method has already been shown to significantly reduce numbers of D. suzukii in open strawberry polytunnels by 91% throughout the season when compared with untreated control sites (Homem et al, 2022). This technique could be used with repeated releases in non-crop habitats to intercept newly emerged females from wild hosts before they enter the crop (Nikolouli et al, 2018).…”
Section: Land Management Recommendationsmentioning
confidence: 99%
“…Consistent releases of sterile males could outcompete fertile males with the aim of reducing populations of D. suzukii in the crop. This method has already been shown to significantly reduce numbers of D. suzukii in open strawberry polytunnels by 91% throughout the season when compared with untreated control sites (Homem et al, 2022). This technique could be used with repeated releases in non-crop habitats to intercept newly emerged females from wild hosts before they enter the crop (Nikolouli et al, 2018).…”
Section: Land Management Recommendationsmentioning
confidence: 99%
“…Recently. Homem et al (2022) indeed reported that sterile releases hampered D. suzukii population growth in a (single) large greenhouse, which was compared to two control greenhouses. This earlier work is particularly impressive for the scale of the assay and the number of insects produced and released.…”
Section: Discussionmentioning
confidence: 97%
“…Standard statistical methods could hence be deployed ; they show, with little doubt, that the SIT is efficient at reducing D suzukii reproduction. This occurred even at a fairly low sterile/fertile ratio of 5, much lower than that used by Homem et al (2022). Moreover, because the assay was run over less than 1 fly generation (5 days) we could control numerous parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dose can be decreased if the adults are infected with Wolbachia bacteria (Nikolouli et al, 2020). Recently, releases of sterile males suppressed the wild female SWD population by up to 91% (Homem et al, 2022). However, that did not stop the females from damaging the fruits via oviposition allowing the infection of the fruit by bacteria or fungi (Cini et al, 2012;Lanouette et al, 2017).…”
Section: Sterile Insect Releasementioning
confidence: 99%